Estimating informal household food waste in developed countries: The case of Australia. Issue 12 (December 2014) - Reynolds, Christian J; Mavrakis, Vicki; Davison, Sandra; Høj, Stine B; Vlaholias, Elisha; Sharp, Anne; Thompson, Kirrilly; Ward, Paul; Coveney, John; Piantadosi, Julia; Boland, John; Dawson, Drew
Food waste is a global problem. In Australia alone, it is estimated that households throw away AU$5.2 billion worth of food (AU$616 per household) each year. Developed countries have formal waste management systems that provide measures of food waste. However, much remains unknown about informal food waste disposal routes and volumes outside of the formal system. This article provides indicative metrics of informal food waste by identifying, in detail, five of the dominant informal food waste disposal routes used by Australian households: home composting, feeding scraps to pets, sewer disposal, giving to charity, and dumping or incineration. Informal waste generation rates are then calculated from three primary data sources, in addition to data from previous Australian and UK surveys, using a weighted average method in conjunction with a Monte-Carlo simulation. We find that the average Australian household disposes of 2.6 kgs of food waste per week through informal routes (1.7 kgs via household composting, 0.2 kgs via animals, and 0.6 kgs via sewage). This represents 20% of Australian household food waste flows. Our results highlight that informal food waste is a sizable food waste flow from Australian homes, deserving of greater research and government attention. Our examination of the full extent of food waste by disposal mode provides waste managers and policy makers with clear disposal routes to target for behaviour change and positive environmental outcomes.